Divorce laws in Malaysia - Kamaruddin, Zaleha (Malayan Law Journal Sdn Bhd, 2005)
The aim of this book is to define the outline of the history of divorce laws in Malaysia, without losing sight that divorce must be carefully integrated into a much broader context. A knowledge of that background helps to explain why the law is as it is, but it does not necessarily provide a justification for it to remain unchanged in those areas where reforms may be considered desirable. This has been done by focusing critically on divorce in the Malaysian society. The discussion in this book is divided into two; the Civil Law which is applicable to Non-Muslims and Islamic Law Rfor the Muslims. From the civil law perspective, although the Law Reform (Marriage and Divorce) ACT, 1976 has brought fundamental changes, reforms in divorce law, so far have been confined to the substantial aspects of the law without any consideration as regards the judicial institutions which administer the law. This book highlights possible reforms to improve certain areas of the law. As for divorce law relating to Muslims, although it has improve greatly, unfortunately there are some areas in the administration of Islamic Family Law that need to be further reformed to suit the needs of modern society.